The Holm Oak leaf proteome: Analytical and biological variability in the protein expression level assessed by 2-DE and protein identification tandem mass spectrometry de novo sequencing and sequence similarity searching - Jorge, Inmaculada; Navarro, Rafael M; Lenz, Christof; Ariza, David; Porras, Carlos; Jorrín, Jesús (PROTEOMICS, 2005)
As a first approach in establishing the holm oak leaf proteome, we have optimised a protocol for this plant and tissue which includes the following steps: trichloroacetic acid-acetone extraction, two-dimensional gel electrophoresis (2-DE) on pH 5 to 8 linear gradient immobilised pH gradient strips as the first dimension, and sodium dodecyl sulfate-polyacrylamide gel electrophoresis on 13% polyacrylamide gels as the second one. Proteins were detected by Coomassie staining. Gel images were recorded and digitalized, and the protein spots quantified by using a linear regression equation of protein quantity on spot volume obtained against standard proteins. Analytical variance was calculated for one-hundred protein spots from three replicate 2-DE gels of the same protein extract. Biological variance was determined for the same protein spots from independent tissue extracts corresponding to leaves from different trees, or the same tree at different orientations or sampling times during a day. Values of 26% for the analytical variance and 58.6% for the biological variance among independent trees were obtained. These values provide a quantified and statistical basis for the evaluation of protein expression changes in comparative proteomic investigations with this species. A representative set of the major proteins, covering the isoelectric point range of 5 to 8 and the relative molecular massr range of 14 to 78 kDa, were subjected to liquid chromatography-tandem mass spectrometry analysis. Due to the absence of Quercus DNA or protein sequence databases, a method based on the procedure reported by Liska and Shevchenko [1] including de novo sequencing and BLAST similarity searching against other plant species databases was used for protein identification. Out of 43 analysed spots, 35 were positively identified. The identified proteins mainly corresponded to enzymes involved in photosynthesis and energetic metabolism, with a significant number corresponding to RubisCO.
Keywords: De novo sequencing; Holm oak; Leaf proteome; Tandem mass spectrometry; Two-dimensional gel electrophoresis